Phase I study of axitinib and everolimus in metastatic solid tumours and extension to metastatic renal cell carcinoma: Results of EVAX study. (November 2017) - Ravaud, Alain; Gomez-Roca, Carlos; Picat, Marie-Quitterie; Digue, Laurence; Chevreau, Christine; Gimbert, Anne; Chauzit, Emmanuelle; Sitta, Rémi; Cornelis, François; Asselineau, Julien; Aziza, Richard; Daste, Amaury; et al.
Abstract: Purpose: Anti-angiogenic and mammalian target of rapamycin inhibitors have shown efficacy in solid tumours. Reported combination of both drugs was deemed to be too toxic. Due to a potential favourable safety profile of axitinib (AX), a phase I study combining everolimus (EV) and AX for solid tumours was explored. Experimental design: Patients (pts) with advanced cancers were enrolled in an escalation phase I study to investigate the safety of the combination. Pharmacokinetic profile and functional vascular imaging were performed. An extension to pts with naive metastatic renal cell carcinoma (MRCC) was explored. Results: 15 pts were included over three different dose levels (DLs); DL 0: AX 3 mg BID (twice daily)/EV 5 mg OD (once daily); DL 1: AX 5 mg BID/EV 5 mg OD and DL 2: AX 5 mg BID/EV 10 mg OD for 28 d. One dose-limiting toxicity (DLT) was reported at DL 0: grade (Gr) III diarrhoea and one DLT at DL 2: Gr III asthenia. Three severe adverse events (AEs) in two pts were unexpected: jaw osteonecrosis, recurrent renal failure and cardiomyopathy. Maximum tolerated dose (MTD) was level 2. After 1st cycle, Gr III or Gr II AEs of interest were mainly asthenia, diarrhoea and anorexia. All pts but one showed tumour shrinkage. Partial responses (PRs) were seen in one pt with bladder carcinoma and in one pt in 1st line MRCC in the escalating phase. In the extension phase in naive MRCC treated at MTD, five pts had a PR and one pt had a prolonged stable disease. Conclusion: The recommended dose for phase II is AX 5 mg BID/EV 10 mg OD. Highlights: Axitinib (AX) and everolimus (EV) can be associated at the standard dose of each drug. Association can be given at the standard dose for prolonged subsequent cycles. Combination of AX and EV is efficient in metastatic renal cell carcinoma.